Proses Produksi dan Penjualan Batako dalam Perspektif Hukum Islam dan Konsumen: Sebuah Kajian Hukum - Ahmad Zainuri; Lukman Santoso (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2019)
Purpose- This article aims to review how to review Islamic business ethics and consumer protection laws for the brick production process and how to review Islamic business ethics and consumer protection laws for the brick sales process in Nguneng Village, Wonogiri. Methods- This research is a type of field research with a qualitative approach, data collection techniques using observation and interviews related to the production and sale of the concrete block. Then conclude using theories of Islamic business ethics and consumer protection laws. Findings- Based on the results of the study it can be concluded that 1) The process of brick production in Nguneng Village, Puhpelem District Wonogiri Regency is not following Islamic business ethics because it does not meet the principles of Islamic business ethics, because it pays little attention to honesty, balance, free will, responsibility, and virtue in making Concrete brick. According to the Law, consumer protection is not following Article 7 because business actors do not have good intentions in conducting their business. 2) The brick sales process is not following the principles of Islamic business ethics because it does not meet the principles of honesty, balance, responsibility, and virtue and violates several articles The consumer protection law is following article 8 and also does not comply with the obligations of business actors in article 7 because it does not guarantee the quality of goods and services produced. Consumers also have the right to consumer protection in Article 4 because consumer rights are not fulfilled.